Concerted Effort on Conflict Approaches: An Ubuntu Theory that Generates New Approaches in the Fourth Industrial Revolution Era (Journal of Governance and Development (JGD), 2019)
The rapid pace of the industrial growth frolicked a crucial role in the previous conï¬‚ict approaches. However, conï¬‚ict approaches are expected to transform in terms of technological change and socioeconomic impact. The current conï¬‚ict approaches are dominated by Western theories created for individualist cultures that stand in contrast to the communal culture of African and Asian citizens. As a result, Afrocentric and Asia centric theories are under threat from the proliferation of foreign ideologies and concepts, which have long inï¬‚uenced conï¬‚ict approaches. The methodology on the Ubuntu practical applicant generates new perspectives on conï¬‚ict approaches in the fourth industrial revolution era. Quester-views, focus group discussions (FGD) and discussions were used as data collection tools. The data was managed using the Computer Assisted Qualitative Data Analysis Software (CAQDAS) package, which is a qualitative data-management and analysis tool. The tendency has been to concentrate analyses around prevention, management and resolutions with little reference to the fundamental consensus-building blocks of a social value system within the fourth industrial revolution era. As a result, this conï¬‚ict approaches in this article should be accepted within the African indigenous local knowledge system on Ubuntu in African terms.